Long-Term Outcome of Patients With Chronic Thromboembolic Pulmonary Hypertension: Results From an International Prospective Registry. Issue 9 (1st March 2016) - Delcroix, Marion; Lang, Irene; Pepke-Zaba, Joanna; Jansa, Pavel; D'Armini, Andrea M.; Snijder, Repke; Bresser, Paul; Torbicki, Adam; Mellemkjaer, Sören; Lewczuk, Jerzy; Simkova, Iveta; Barberà, Joan A.; et al.
Abstract : Background—: Chronic thromboembolic pulmonary hypertension, a rare complication of acute pulmonary embolism, is characterized by fibrothrombotic obstructions of large pulmonary arteries combined with small-vessel arteriopathy. It can be cured by pulmonary endarterectomy, and can be clinically improved by medical therapy in inoperable patients. A European registry was set up in 27 centers to evaluate long-term outcome and outcome correlates in 2 distinct populations of operated and not-operated patients who have chronic thromboembolic pulmonary hypertension. Methods and Results—: A total of 679 patients newly diagnosed with chronic thromboembolic pulmonary hypertension were prospectively included over a 24-month period. Estimated survival at 1, 2, and 3 years was 93% (95% confidence interval [CI], 90–95), 91% (95% CI, 87–93), and 89% (95% CI, 86–92) in operated patients (n=404), and only 88% (95% CI, 83–91), 79% (95% CI, 74–83), and 70% (95% CI, 64–76) in not-operated patients (n=275). In both operated and not-operated patients, pulmonary arterial hypertension–targeted therapy did not affect survival estimates significantly. Mortality was associated with New York Heart Association functional class IV (hazard ratio [HR], 4.16; 95% CI, 1.49–11.62; P =0.0065 and HR, 4.76; 95% CI, 1.76–12.88; P =0.0021), increased right atrial pressure (HR, 1.34; 95% CI, 0.95–1.90; P =0.0992 and HR, 1.50; 95% CI, 1.20–1.88; P =0.0004), and a history of cancer (HR, 3.02; 95% CI, 1.36–6.69; P =0.0065 and HR, 2.15; 95% CI, 1.18–3.94; P =0.0129) in operated and not-operated patients, respectively. Additional correlates of mortality were bridging therapy with pulmonary arterial hypertension–targeted drugs, postoperative pulmonary hypertension, surgical complications, and additional cardiac procedures in operated patients, and comorbidities such as coronary disease, left heart failure, and chronic obstructive pulmonary disease in not-operated patients. Conclusions—: The long-term prognosis of operated patients currently is excellent and better than the outcome of not-operated patients. Abstract : Supplemental Digital Content is available in the text.